Hustle Culture in Social Media: Exploring the Imagined Success in the Modern Era - Athifah Chairunnisah; Lilawati Kurnia (CV. Media Digital Publikasi Indonesia, 2023)
This study examines how the notion of success among modern Indonesian youth, particularly the millennial generation, is constructed through the hustle culture trend on social media. With social media playing a significant role in shaping the aspirations and lifestyles of young individuals, the study centers on the hustle culture trend due to its strong promotion of values such as hard work, ambition, and productivity as integral to their way of life. Data was collected from various platforms including Instagram, Twitter, and TikTok, comprising textual, visual, and multimedia content related to hustle culture and the modern urban youth lifestyle in Indonesia. Additionally, interviews were conducted with six millennial respondents. The collected data is analyzed using the Ethnography Content Analysis (ECA) approach while reflecting on various theoretical concepts regarding youth, urban, social media, and hustle culture. The findings demonstrate that the hustle culture trend constructs an idealized image and lifestyle of modern urban youth, portraying them as modern, productive, and inspirational, thereby equating the social media image of success with actual success. This research provides a fresh perspective on understanding success among Indonesian youth in the modern era, specifically by examining the influence of social media practices in their daily lives